2020
DOI: 10.2139/ssrn.3656964
|View full text |Cite
|
Sign up to set email alerts
|

From Shattered Goals to Meaning in Life: Life Crafting in Times of the COVID-19 Pandemic

Abstract: The novel COVID-19 pandemic has created an extraordinary situation for our generation, with many countries being on lockdown. With this new situation comes many psychological challenges, not only for health care workers and people suffering from COVID-19, but also for the general population. Adapting to the new situation can be demanding. Experts have suggested that emotions during this situation are very similar to grief, and people experience emptiness and sadness about the loss of their normal lives, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The inability to achieve one's life goals can lead to a sense of despair and a lack of purpose ( Steger, 2017 ). In general, attainment of life goals has been shown to have many benefits for mental as well as physical well-being ( De Jong et al., 2020 ), especially during a crisis such as the COVID-19 pandemic ( Trzebiński et al., 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…The inability to achieve one's life goals can lead to a sense of despair and a lack of purpose ( Steger, 2017 ). In general, attainment of life goals has been shown to have many benefits for mental as well as physical well-being ( De Jong et al., 2020 ), especially during a crisis such as the COVID-19 pandemic ( Trzebiński et al., 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…Those who rated the impact as high had higher stress and mental health scores of anxiety and depression. Regarding intangible existence, it is notable that from other studies not only feelings of boredom were reported facing the COVID-19 pandemic [56,57], but also feelings of emptiness and sadness about the loss of normal life, which can even lead to a loss of meaning in life [58].…”
Section: Risk Distribution In Different Student Groupsmentioning
confidence: 94%
“…Second, there is the relationship to religion to consider. People in crisis situ ations, such as the COVID-19 pandemic, seem to be more likely to experience a loss of meaning in life (de Jong et al 2020;Schnell and Krampe 2020), and the role of religion in managing the emotional and social fallout of a crisis seems more clear-cut, as a traditional route for handling the crisis and loss of meaning.…”
Section: Conspiracy Theory Religion and Covid-19mentioning
confidence: 99%